Essence or experience? A new direction for African psychology. (June 2017) - Long, Wahbie
This article examines the attempts of psychologists in South Africa to "Africanize" the discipline. Beginning with a brief history of psychology on the continent, it contextualizes the call for an African psychology by outlining the state of the broader discipline in post-apartheid South Africa as well as the emergence of Afrocentric psychology in the United States. The article interrogates further the notion of an "African worldview" and suggests that Afrocentric psychologists remain beholden to Eurocentric audiences—the result of their continued marginalization by a Eurocentric discipline. Drawing on Fanon's image of a Manichean psychology, the paper argues that African psychology—instead of organizing itself around cultural questions—must commit itself to a psychological analysis of the violence that exemplifies life in South Africa.